Novel Bacillus subtilis Spore-Displayed Tyrosinase Kit for Rapid Detection of Tyrosine in Urine: Pharmaceutical Applications for the Early Diagnosis of Kidney-Related Diseases - Maziyar Tayebi; Afrouzossadat Hosseini Abari; Giti Emtiazi; Byung Gee Kim; Junehyung Kim (Tabriz University of Medical Sciences, 2019)
Purpose: Simple and cheap diagnostic kit development is one of the important aims of pharmaceutical developers and companies focused on public health improvement. The Bacillus subtilis spore surface-display technique is a genetic engineering method that is used to develop new-generation diagnostic kits applicable for the early detection of various types of diseases. In this study, we developed a novel simple, rapid, and inexpensive diagnostic paper-based kit to detect tyrosine in urine samples of humans and animals that is applicable for home or laboratory use. Methods: The B. subtilis spore-displayed tyrosinase system developed by genetic engineering methods was used to prepare a paper-based kit to detect tyrosine in urine samples of different groups of patients (i.e., patients with diabetes, diabetes with chronic kidney disease (CKD), and chronic kidney disease) for the detection of tyrosine during the acute disease phase. To confirm the sensitivity and specificity of the kit, tyrosine was also detected in urine samples using conventional liquid chromatography/mass spectroscopy. Results: Different concentrations of tyrosine (0.1-1 mM) were detected in urine samples based on visible changes of color from bright brownish-gray to dark brownish-gray within 1 hour. The kit could screen samples to distinguish the three groups of patients based on formation of a broad spectrum of colors reflecting the concentration of tyrosine. Conclusion: To the best of our knowledge, this is the first diagnostic kit with potential to rapidly diagnose various diseases related to the production of tyrosine in biological samples. This kit is not only widely applicable, including for personal use in the home, but is also appropriate as a part of standard screening tests and health protection programs in countries with limited resources.